Ecological evaluation of transitional and coastal waters: A marine benthic macrophytes-based model - ORFANIDIS, S.; PANAYOTIDIS, P.; STAMATIS, N. (Mediterranean Marine Science, 2001)
A model to estimate the ecological status and identify restoration targets of transitional and coastal waters was developed. Marine benthic macrophytic species (seaweeds, seagrasses) were used to indicate shifts in the aquatic ecosystem from the pristine state with late-successional species (Ecological State Group I) to the degraded state with opportunistic (ESG II) species. The first group comprises species with a thick or calcareous thallus, low growth rates and long life cycles (perennials), whereas the second group includes sheet-like and filamentous species with high growth rates and short life cycles (annuals). Seagrasses were included in the first group, whereas Cyanophyceae and species with a coarsely branched thallus were included in the second group. The evaluation of ecological status into five categories from high to bad includes a cross comparison in a matrix of the ESGs and a numerical scoring system (Ecological Evaluation Index). The model could allow comparisons, ranking and setting of priorities at regional and national levels fulfilling the requirements of the EU Water Frame Directive. A successful application of the model was realized in selected lagoons of the Macedonian and Thrace region (North Greece) and in the Saronic Gulf coastal ecosystems (Central Greece).